Fabrication and characterization of organic single crystal field-effect transistors - Zhang, Keke (2013)
Rubrene, a poly-aromatic hydrocarbon, is studied in this thesis. Purity of commercial rubrene powder and rubrene single crystals, grown by PVT technique, were investigated by means of high performance liquid chromatography and mass spectroscopy. High quality rubrene single crystals were used to fabricate Si / SiO2 and air-gap transistors based on pre-patterned PDMS stamp. On such transistor architecture, rubrene single crystal shows mobility as high as 19 cm2/Vs. Electrical properties displayed dramatic changes in the presence of different gas environments. The effects of O2, H2, CO, NO2 and H2S gas were studied. In the presence of oxidative gas, mobility remains high while in reductive gas, mobility drops to a lower value. The high mobility of rubrene FETs measured in ambient environment may not reflect its intrinsic behavior but is a consequence of the oxidation states on the rubrene surface.